2018
DOI: 10.1002/ijgo.12502
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord arterial base deficit and arterial pH as predictors of adverse outcomes among term neonates

Abstract: ABD demonstrated no predictive value for adverse neonatal outcomes beyond using arterial pH alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…When the adherence score obtained by patients with STI reaches 9, we believe that the patient would perform well with good adherence. The same methods for evaluating the predictive value of indicators have been used previously [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…When the adherence score obtained by patients with STI reaches 9, we believe that the patient would perform well with good adherence. The same methods for evaluating the predictive value of indicators have been used previously [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…A study in the United States showed that the neonatal admission rate at > 34 weeks is around 10% but varies greatly from 1.1 to 37% across NICUs and only 11% of those admissions were associated with high illness acuity criteria [ 34 ]. Low arterial cord blood pHs have been associated with more complications especially NICU admissions and seizures [ 35 , 36 ]. Nonetheless some authors [ 37 , 38 ] concluded that neonatal morbidity with an arterial cord blood pH < 7 can only be predicted when associated with low five-minute Apgar score and/or an important arterial cord blood base deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The same methods for evaluating the predictive value of indicators have been used previously. [30][31][32][33] Use of the PrEP adherence questionnaire provides the opportunity to evaluate patients' adherence in advance, such that a patient with low adherence can be detected prior to starting PrEP therapy. Individualbased measures can be used to improve adherence or to detect the need to use prevention measures other than PrEP, which could be more suitable for an individual and yield greater bene ts.…”
Section: Discussionmentioning
confidence: 99%